Highly stretchable wrinkled electrode based on silver ink‐elastomer nanocomposite with excellent fatigue resistance. Issue 6 (3rd February 2020) - Won, Joohye; Mondal, Subhadip; Park, Jongho; Wang, Wonseok; Lee, Hyunsang; Kim, Suhyun; Shin, Beomsu; Sathi, Shibulal G.; Nah, Changwoon
Abstract: Flexible and stretchable electrodes have attracted immense attention because of their various electronic applications on the wearable sensing electronics, but challenges regarding robust and sustainable electrical performance under static and dynamic mechanical stresses still need to be overcome. Herein, with a simple effective strategy, a highly serviceable and flexible elastomeric electrode fabricated by utilizing an interpenetrating network between acrylic rubber (AR) and silicone rubber (SR), and silver (Ag) ink to increase electrical conductivity, is introduced. Oxygen (O2 ) plasma and sodium dodecyl sulfate (SDS) treatment on wrinkle substrate surface lead to robust adhesion of Ag ink layer, results in high electrical conductivity. Wrinkle morphology can help to stably maintain the continuous conductive Ag network during static and dynamic deformation. This stretchable electrode possessing properties such as robust and stable electrical conductivity of ~10 3  S/cm under 150% static tensile deformations and good sustainability after 1000 cycles of dynamic tensile deformations is a promising candidate for stretchable wearable electronics.